Three -dimensional catalytic oxidation processing system of domestic sewage - WU ZHENGHAO; WU YONG; GAO DONGDONG; WANG XIAOTONG (2017)
The utility model relates to a sewage treatment field, concretely relates to three -dimensional catalytic oxidation processing system of domestic sewage. The utility model provides a three -dimensional catalytic oxidation processing system of domestic sewage, include plastid filtering layer artificially, the plastid filtering layer includes the sewage treatment module of a plurality of adjacent settings artificially, and every sewage treatment module includes the multi - layer packing layer, and the array orientation of the packing layer of arbitrary two adjacent sewage treatment modules is different in the plastid filtering layer artificially. The utility model discloses a plastid filtering layer comprises the sewage treatment module of a plurality of permutation and combination artificially, and the array orientation of the packing layer of arbitrary two adjacent sewage treatment modules is different, not equidirectional packing layer has increased the catalytic oxidation response surface, sewage produces w